Production Process of Large Pore Size Activated Carbon from Palm Kernel Shell using Sodium Chloride as An Activator - Nurdin, Ahmad; Iriani, Iriani; Harahap, Hamidah; Fahmi, Aliyah (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
This study aimed to determine the yield of activated carbon, iodine number, and surface area of palm activated carbon. Samples were produced by using sodium chloride (NaCl) as an activator. Palm shells that had been produced by the milling process were then sieved with a 12 mesh sieve and soaked in 20 % NaCl solution. The sample solution was heated over a water bath at 70 oC and continued with the drying process at a constant temperature of 105 oC. The activated shells continued the pyrolysis process at temperatures of 300, 400, and 500 oC for 3 hours. The activated carbon obtained from the pyrolysis process was weighed and then washed using hot distilled water. The samples were dried in an oven at a temperature of 105 oC for 24 hours. The results were analyzed for iodine number using iodometric titration method, surface area using Brunauer- Emmett-Teller (BET) method, and pore structure using the Scanning Electron Microscope (SEM) method. The results showed the best yield was 38.13 % obtained at 20% NaCl and a temperature of 400 oC. The best iodine number was 767.745 mg/g and surface area was 6.790 m2/g, pore volume 4.377 cc/g with pore size 9.781 A.